Clinical commentary: depression and anxiety in adolescent and young adult athletes - Putukian, M.; Yeates, K. O. (Journal of Athletic Training, 2023)
Key Points: Mental health (MH) symptoms and disorders, specifically depression and anxiety, are common in adolescent and young adult athletes. Sport medical staff (eg, athletic trainers/therapists and team physicians) can provide critical MH services to athletes and play an important role in education about MH conditions and their recognition, treatment, and prevention. Understanding the role of screening for MH conditions, as well as policies regarding MH plans and MH emergency action plans, is necessary for the sports medicine team.